2018
DOI: 10.1101/338400
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Astrocytes promote a protective immune response to brainToxoplasma gondiiinfection via IL-33-ST2 signaling

Abstract: SUMMARY 21An intact immune response is critical for survival of hosts chronically infected with 22Toxoplasma gondii. We observe clusters of macrophages surrounding replicating parasite in brain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 90 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…Microglia have also been demonstrated to possess some potentially anti-parasitic functions [27][28][29][30][31] , but we are interested in investigating whether microglia perform specific, nonoverlapping functions distinct from infiltrating macrophages. Previous work from our lab has observed that while bloodderived monocytes and macrophages express high levels of the nitric oxide-generating enzyme iNOS in the brain during T. gondii infection, microglia lack this anti-parasitic molecule 43 . We hypothesize that even though they are in the same tissue microenvironment, microglia are unable to respond to the infection in the same way as infiltrating macrophages.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Microglia have also been demonstrated to possess some potentially anti-parasitic functions [27][28][29][30][31] , but we are interested in investigating whether microglia perform specific, nonoverlapping functions distinct from infiltrating macrophages. Previous work from our lab has observed that while bloodderived monocytes and macrophages express high levels of the nitric oxide-generating enzyme iNOS in the brain during T. gondii infection, microglia lack this anti-parasitic molecule 43 . We hypothesize that even though they are in the same tissue microenvironment, microglia are unable to respond to the infection in the same way as infiltrating macrophages.…”
Section: Resultsmentioning
confidence: 80%
“…It has also been suggested that IL-1 can act on neurons, though it should be noted that it has also been reported that neurons express a unique form of IL-1RAcP which affects downstream signaling 69 . It is unclear whether astrocytes express IL-1R1, but astrocytes represent another radio-resistant cell population in the brain that has the ability to affect immune cell infiltration through chemokine production 14,43 . e Cyst burden per brain was determined by counting cysts in brain homogenate on a light microscope.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work from our lab has observed that while blood-derived monocytes and macrophages express high levels of the nitric oxide-generating enzyme iNOS in the brain during T. gondii infection, microglia markedly lack this anti-parasitic molecule. 29 This observation led to the hypothesis that even though they are in the same tissue microenvironment, microglia are unable to respond to the infection in the same way as infiltrating macrophages. Thus, we used a CX3CR1 Cre-ERT2 x ZsGreen fl/stop/fl mouse line that has been previously described as a microglia reporter line.…”
Section: Resultsmentioning
confidence: 99%
“…61 It is unclear whether astrocytes express IL-1R1, but astrocytes represent another radio-resistant cell population in the brain that has the ability to affect immune cell infiltration through chemokine production. 29, 62…”
Section: Discussionmentioning
confidence: 99%
“…32,[35][36][37] While reactive astrocytes can be beneficial as in the case of spinal cord injury by forming a barrier between healthy and necrotic tissue or in Toxoplasma gondii infection by producing chemokines to recruit helpful immune cells, reactive astrocytes can also be detrimental. 38,39 A common feature of reactive astrocytes is the downregulation of genes involved in maintaining CNS homeostasis such as K ir 4.1, aquaporin 4, and neurotransmitter transporters and degrading enzymes. 40 Loss of the homeostatic functions of astrocytes is the most prominent feature of reactive astrocytes in epilepsy.…”
Section: Discussionmentioning
confidence: 99%